VMAT optimization with dynamic collimator rotation. Issue 6 (3rd May 2018) - Lyu, Qihui; O'Connor, Daniel; Ruan, Dan; Yu, Victoria; Nguyen, Dan; Sheng, Ke
Abstract : Purpose: Although collimator rotation is an optimization variable that can be exploited for dosimetric advantages, existing Volumetric Modulated Arc Therapy (VMAT) optimization uses a fixed collimator angle in each arc and only rotates the collimator between arcs. In this study, we develop a novel integrated optimization method for VMAT, accounting for dynamic collimator angles during the arc motion. Methods: Direct Aperture Optimization (DAO) for Dynamic Collimator in VMAT (DC‐VMAT) was achieved by adding to the existing dose fidelity objective an anisotropic total variation term for regulating the fluence smoothness, a binary variable for forming simple apertures, and a group sparsity term for controlling collimator rotation. The optimal collimator angle for each beam angle was selected using the Dijkstra's algorithm, where the node costs depend on the estimated fluence map at the current iteration and the edge costs account for the mechanical constraints of multi‐leaf collimator (MLC). An alternating optimization strategy was implemented to solve the DAO and collimator angle selection (CAS). Feasibility of DC‐VMAT using one full‐arc with dynamic collimator rotation was tested on a phantom with two small spherical targets, a brain, a lung and a prostate cancer patient. The plan was compared against a static collimator VMAT (SC‐VMAT) plan using three full arcs with 60 degrees of collimator angle separation in patient studies. Results: With the same target coverage, DC‐VMAT achieved 20.3% reduction of R50 in the phantom study, and reduced the average max and mean OAR dose by 4.49% and 2.53% of the prescription dose in patient studies, as compared with SC‐VMAT. The collimator rotation co‐ordinated with the gantry rotation in DC‐VMAT plans for deliverability. There were 13 beam angles in the single‐arc DC‐VMAT plan in patient studies that requires slower gantry rotation to accommodate multiple collimator angles. Conclusions: The novel DC‐VMAT approach utilizes the dynamic collimator rotation during arc delivery. In doing so, DC‐VMAT affords more sophisticated intensity modulation, alleviating the limitation previously imposed by the square beamlet from the MLC leaf thickness and achieves higher effective modulation resolution. Consequently, DC‐VMAT with a single arc manages to achieve superior dosimetry than SC‐VMAT with three full arcs.